Self-regulation of the medical and legal professions: Remaining barriers to competition and EC-law - Roger J. VanDenBergh (Fondazione Eni Enrico Mattei (FEEM), 1997)
In the Gebhard judgement the European Court of Justice has formulated the requirements which must be satisfied for self-regulatory restrictions on entry (such as the protection of titles and compulsory membership of public professional bodies) to be compatible with the fundamental freedoms guaranteed by the EC-Treaty. The paper suggests how the legal criteria may be clarified by economic insights to enable a better assessment of their conformity with the EC Treaty. To demonstrate that regulation is needed for imperative reasons of public interest, it should be shown that the self-regulatory measures are able to cope with market failures (information asymmetries, externalities). To show that the measures go not beyond what is necessary to attain this goal (requirement of proportionality), it should be shown that there are no alternative rules which cope with the relevant market failures as effectively as the current rules, without causing the same inefficiencies.
Keywords: 330; Regulierung; Markteintritt; Gesundheitsberufe; Rechtsberufe; EU-Staaten